COMPARATIVE EFFECTS OF NITRAZEPAM AND ACTH ON THE TREATMENT OF INFANTILE SPASM - Taghdiri MD, MM.; Ghofrani MD, M.; Abbasi MD, B.; Zandevakili MD, H. (Iranian Journal of Child Neurology, 2009)
Objective Infantile spasms (IS) or West syndrome is a convulsive disease characterized by brief, symmetric axial muscle contractions (neck, trunk, and/or extremities).The therapy universally recognized as most effective in the treatment of IS, is treatment with the adrenocorticotropic hormone (ACTH) or oral corticosteroids. This therapy however has important side effects. Many studies have sought to find alternative therapies with fewer side effects. Nitrazepam, it has been proven, can be as effective as ACTH in controlling infantile spasms. The aim of this study was to evaluate and compare the efficacy of Nitrazepam and ACTH on the treatment of infantile spasms. Materials & Methods This randomized controlled clinical trial, enrolled sixty patients with newly diagnosed and previously untreated IS; diagnosis was made based on the criteria of The International Classification of Epilepsies of the International League Against Epilepsy (ILAE). Prior to treatment, all patients underwent Electro encephalo graphs (EEGs) and CT scans. Patients were randomized to receive 0.5-1 mg/kg Nitrazpam (NZP) in three daily doses or 40 IU Depot ACTH in a single morning dose. Complete cessation of spasms was considered to be as optimal response. Results Of the sixty patients studied, 24 (40%) were girls and 36(60%) were boys. All patients in the both groups were matched for age and sex.There were no differences between the both groups regarding age and sex (non-significant). Following treatments, at the end of the 6-week duration therapy, optimal response (Cessation of spasms) was obtained in 19 (63%) patients of NZP group and 9 (30%) patients of ACTH group, (P<0.05). ACTH side effects were more pronounced than those of NZP; Most patients in ACTH group, developed cushingoid features (moon face 93%, weight gain 100%)(P<0.05); a few patients,all from the ACTH group, developed hypertension (P<0.05). The side effects of nitrazepam were drowsiness 33%, hypotonia 10%, infection 20%, and hypersalivation 93%. EEG anomalies had disappeared in 47% of NZP patients and in 30% of ACTH patients (P>0.05). Conclusion This study supports the belief that NZP offers an effective and possibly safer therapy than ACTH, for the management of IS and that the therapeutic response, if imminent, can be detected within 4-6 weeks of treatment. Clinicians should consider using NZP as a first-line therapy for IS. Keywords: Corticotropin /Spasms, Infantile / Nitrazepam